Biocatalytic Application of a Membrane‐Bound Coumarin C‐Glucosyltransferase in the Synthesis of Coumarin and Benzofuran C‐Glucosides. Issue 22 (23rd April 2021) - Chen, Dawei; Fan, Shuai; Yang, Zhaoyong; Dai, Jungui
Abstract: A number of plant C‐glycosyltransferases (CGTs) have been recently identified, whereas the coumarin CGTs have not been found. Here we reported the first identification of a coumarin C‐glucosyltransferase MaCGT from Morus alba . The whole‐cell biocatalyst harboring MaCGT was exploited and exhibited strictly and efficiently regio‐ and stereo‐specific C‐glucosylation capacity toward structurally different coumarins. The whole‐cell of MaCGT was further applied to chemo‐enzymatically synthesize benzofuran C‐glucosides. Moreover, MaCGT is reported as the first characterized membrane‐bound CGT from plants, although sequence homology search has shown other potentially membrane‐bound CGTs from M. notabilis ; and the presence of the transmembrane domain is critical for its catalytic activity and stability as demonstrated by the C‐glucosylation activity of truncated MaCGT proteins. In addition, the key residues involved in the C‐glucosylation of MaCGT were explored. These findings suggest the diversity of CGTs in the plant kingdom and demonstrate the significant potential of biocatalytic approach to produce structurally diverse C‐glycosides for drug discovery. Abstract :